Immunisation of mares with binding domains of toxins A and B of Clostridium difficile elicits serum and colostral antibodies that block toxin binding. (4th December 2012) - Artiushin, S.; Timoney, J. F.; Fettinger, M.; Fallon, L.; Rathgeber, R.
Summary Reasons for performing study Enterocolitis caused by Clostridium difficile (C. difficile) is a serious, sometimes fatal, disease of neonatal foals and older horses. Toxins A and B (TcdA and B) produced by C. difficile are important virulence factors. Immunisation of mares with receptor binding domains of toxins may prevent or reduce the severity of C. difficile colitis in foals. Objectives To determine whether antibodies generated in the pregnant mare to the binding regions of TcdA and B will neutralise TcdA and B toxicity. Methods Sequences encoding the binding domains of each toxin were isolated by PCR amplification from C. difficile JF09, a foal isolate, and cloned and expressed into pET15b. Thirteen mares were immunised twice 2 weeks apart with 200 μg of each recombinant protein with Quil A 2 months prior to foaling. Antibodies were assayed in the sera and colostrum by ELISA and for ability to block the cytopathic activity of each of toxin for equine endothelial cells. Results All mares produced strong serum antibody responses to the binding domain of each toxin. A high level of toxin‐specific antibodies was also detected in colostrum and in most foal sera 2 days after suckling. Diluted sera and colostrum premixed with either TcdA or B had no effect on the morphology of equine endothelial cells. Application of the same concentration of toxins alone or premixed with nonimmune mare/foal serum or colostrum led to an unambiguous cytopathic effect that ranged from complete degradation to varying degrees of cell rounding. Conclusions Immunisation of pregnant mares with recombinant binding domains of TcdA and B of C. difficile resulted in the production of specific antibodies in serum and colostrum that blocked the cytopathic activity of toxins. Potential relevance Results of studies support the feasibility of a prepartum vaccine against C. difficile enterocolitis in foals.